2018
DOI: 10.1590/s0103-73312018280319
|View full text |Cite
|
Sign up to set email alerts
|

Restaurante popular: a política social em questão

Abstract: Resumo As políticas públicas sociais são reconhecidas, nesse ensaio, como imperativas, nos marcos das sociedades capitalistas, para materialização de direitos e necessidades humanas. No Brasil, e nos demais países capitalistas, as políticas sociais se instituíram como desdobramento das lutas de classe, caminho para a conquista de direitos e diminuição de desigualdades. No entanto, dependentes da liberação de recursos públicos, mostram-se fragmentadas e descontínuas. No que tange às políticas sociais, no âmbito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 4 publications
0
18
0
4
Order By: Relevance
“…Despite the relevance of strategies to fight hunger and misery as proposed by the GSR program, the records of periods when several units throughout the country had to be closed are something to be worried about, and the instability sometimes experienced by the equipment, which recently had its information and guidelines taken from government websites. Still, one can wonder about what could be the cause for a certain 'invisibility' of the theme in the available literature [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the relevance of strategies to fight hunger and misery as proposed by the GSR program, the records of periods when several units throughout the country had to be closed are something to be worried about, and the instability sometimes experienced by the equipment, which recently had its information and guidelines taken from government websites. Still, one can wonder about what could be the cause for a certain 'invisibility' of the theme in the available literature [6].…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study carried out between the Brazilian GSR system and the Spanish soup kitchens showed similarities in their objectives, i.e., the distribution of meals to populations with little access to adequate food, aiming to fight hunger and malnutrition [5]. However, when compared to international experiences, the Brazilian proposal has broader characteristics in the use of this equipment, mainly because it is applied as a Food and Nutrition Security (FNS) action, under the spotlight of the Human Right to Adequate Food (HRAF) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such initiatives have different levels of stability; some are established based on public policies, whereas others are temporary programs to aid specific groups. These efforts are designed to reduce social and economic inequality by providing access to sufficient amounts of nutritious food [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, GSR were included in the national program Zero Hunger [8]. From 2006, with the Organic Law of Food and Nutrition Security (LOSAN), some food and nutrition public programs, such as GSR and Food Banks, became essential strategies for fulfilling the human right to adequate food [7]. Therefore, Brazilian GSR are not isolated strategies; instead, they are part of complex and comprehensive public policies that integrate the Brazilian National Food and Nutrition Security Policy (PNSAN) [9].…”
Section: Introductionmentioning
confidence: 99%